Physicians' cancer chemotherapy drug manual 2018 - Chu, Edward; DeVita, Vincent T. (Jones & Bartlett Learning, 2019)
Completely revised and updated for 2018, the Physicians' Cancer Chemotherapy Drug Manual is an up-to-date guide to the latest information on standard therapy and recent advances in the field. Written by world-class experts in clinical cancer therapeutics, this essential reference provides a complete, easy-to-use catalogue of over 100 drugs and commonly used drug regimens--both on- and off-label--for the treatment of all the major cancers.